Determination of Gravity Acceleration with Smartphone Ambient Light Sensor - Silva-Ale, J (Springer International Publishing, 2022)
Among the serious experimental uses given to smartphones in physics, the use of integrated sensors, video analysis, and mixed uses as simultaneous material and instruments stand out for their frequency. Regarding the use of integrated sensors, there are many proposals that use the accelerometer (e.g. Chaps. 32-8) [1-3], the magnetometer (e.g. Chaps. 30 and 34) [4, 5], or other sensors (e.g., camera (Chap. 27) [6] or microphone [e.g. Chap. 12) [7-9]] to find experimental values of physical constants, such as acceleration of gravity (g), thereby trying to contribute to the studies of statics, kinematics, and dynamics. However, there are few studies that use the ambient light sensor for this kind of purpose. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2022. All rights reseverd.